A multimodal screening platform for endogenous dipeptide repeat proteins in C9orf72 patient iPSC neurons - Benedikt V. Hölbling; Yashica Gupta; Paolo M. Marchi; Magda L. Atilano; Michael Flower; Enric Ureña; Rajkumar A. Goulden; Hannah K. Dobbs; Eszter Katona; Alla Mikheenko; Ashling Giblin; Ali Raza Awan; et al. (Cell Reports)
Summary: Repeat expansions in C9orf72 are the most common cause of amyotrophic lateral sclerosis and frontotemporal dementia. Repeat-associated non-AUG (RAN) translation generates neurotoxic dipeptide repeat proteins (DPRs). To study endogenous DPRs, we inserted the minimal HiBiT luciferase reporter downstream of sense repeat derived DPRs polyGA or polyGP in C9orf72 patient iPSCs. We show these “DPReporter” lines sensitively and rapidly report DPR levels in lysed and live cells and optimize screening in iPSC neurons. Small-molecule screening showed the ERK1/2 activator periplocin dose dependently increases DPR levels. Consistent with this, ERK1/2 inhibition reduced DPR levels and prolonged survival in C9orf72 repeat expansion flies. CRISPR knockout screening of all human helicases revealed telomere-associated helicases modulate DPR expression, suggesting common regulation of telomeric and C9orf72 repeats. These DPReporter lines allow investigation of DPRs in their endogenous context and provide a template for studying endogenous RAN-translated proteins, at scale, in other repeat expansion disorders.